2022
DOI: 10.1007/jhep09(2022)142
|View full text |Cite
|
Sign up to set email alerts
|

Sleptonic SUSY: from UV framework to IR phenomenology

Abstract: We study an attractive scenario, “Sleptonic SUSY”, which reconciles the 125 GeV Higgs scalar and the non-observation of superpartners thus far with potentially pivotal roles for slepton phenomenology: providing viable ongoing targets for LHC discovery, incorporating a co-annihilation partner for detectable thermal relic dark matter, and capable of mediating the potential muon g − 2 anomaly. This is accomplished by a modestly hierarchical spectrum, with sub-TeV sleptons and electroweakinos and with multi-TeV ma… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 140 publications
0
4
0
Order By: Relevance
“…While null-results from SUSY searches at the LHC have long excluded strongly charged sparticles (such as gluinos and squarks) in this mass range, LHC searches only recently began putting strong constraints on this range of m for sparticles that interact only electroweakly such as the electroweakinos and smuons that could explain the g-2 anomaly [87,88], and these bounds should improve with further analyses of existing LHC Run2 data as well as with the Run3 data to be recorded in the next years. Future lepton colliders also play an important role for probing electroweak sparticles, especially for (semi-)compressed spectra [89][90][91][92][93][94][95][96][97][98][99][100]. It is worth noting that explanations of the muon g-2 anomalies in the MSSM suggest electroweakinos in the few-hundred GeV mass range, a parameter region of the MSSM yielding viable dark matter candidates [82][83][84][85].…”
Section: Implications Of Anomaliesmentioning
confidence: 99%
“…While null-results from SUSY searches at the LHC have long excluded strongly charged sparticles (such as gluinos and squarks) in this mass range, LHC searches only recently began putting strong constraints on this range of m for sparticles that interact only electroweakly such as the electroweakinos and smuons that could explain the g-2 anomaly [87,88], and these bounds should improve with further analyses of existing LHC Run2 data as well as with the Run3 data to be recorded in the next years. Future lepton colliders also play an important role for probing electroweak sparticles, especially for (semi-)compressed spectra [89][90][91][92][93][94][95][96][97][98][99][100]. It is worth noting that explanations of the muon g-2 anomalies in the MSSM suggest electroweakinos in the few-hundred GeV mass range, a parameter region of the MSSM yielding viable dark matter candidates [82][83][84][85].…”
Section: Implications Of Anomaliesmentioning
confidence: 99%
“…δG F At one-loop order, many operators will be generated. Those most constrained are also relevant for our discussion here, in particular for the S-T-fit, as [50] 95…”
Section: Degenerate Top-squark Soft Massesmentioning
confidence: 99%
“…2 An important theoretical consideration, which we do not consider here, is can g µ −2 be explained in models consistent with grand unification. It was shown that, at least in some unification models, it can be rectified [14,[28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%
“…The CP-problem is solved by assuming a shift symmetry where the imaginary part of the SUSY breaking field receives a constant shift [38]. See also [31] for another construction of a CP-safe gaugino mediation model. 5 In ref.…”
Section: Introductionmentioning
confidence: 99%